2015
DOI: 10.1038/sj.bdj.2015.498
|View full text |Cite|
|
Sign up to set email alerts
|

Practical considerations for conducting dental clinical trials in primary care

Abstract: There is increasing importance placed on conducting clinical trials in dentistry to provide a robust evidence base for the treatment provided, and models of care delivered. However, providing the evidence upon which to base such decisions is not straightforward, as the conduct of these trials is complex. Currently, only limited information is available about the strategies to deliver successful clinical trials in primary care settings, and even less available on dental clinical trials. Considerable knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…The attrition rate in this study, while in line with other similar studies, was high overall (42%) with completion rates in the TAU group lowest at (53%) and the DHE&P group highest at 67%. However, there were no significant differences in demographic characteristics, objective and self‐report of oral hygiene behaviours and social cognitions between women who completed the study and those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…The attrition rate in this study, while in line with other similar studies, was high overall (42%) with completion rates in the TAU group lowest at (53%) and the DHE&P group highest at 67%. However, there were no significant differences in demographic characteristics, objective and self‐report of oral hygiene behaviours and social cognitions between women who completed the study and those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…This presented a challenging setting in which to conduct the study and resulted in a retention rate at 6 months of 46%, which is a study limitation. This is not unusual since recruitment rates, retention and compliance with study protocols have been found to be difficult in other general dental practice trials, even in those located in higher socio-economic areas [20, 21]. Relatively poor understanding about research processes, the model of remuneration in dental practices, time pressures and competing priorities (service vs research) make any type of prospective research in dental practices difficult [22].…”
Section: Discussionmentioning
confidence: 99%
“…A recent non-randomised study in six NHS dental practices which compared a new model involving a traffic light risk assessment of patients, with other practices using the previous model of dental practice care, found only 291 of 550 participants recruited attended both baseline and follow up appointments (53%). This suggests that long term follow up of patients in a study such as this may present challenges [ 50 ]; and recruitment of dental patients to a trial set in dental practice, especially those with a high/medium risk of oral disease, may present further challenges [ 51 ]. Nevertheless, when considered against the continuum of pragmatic as opposed to explanatory trials, this study is designed to be at the pragmatic end of the spectrum, since its purpose is to examine the intervention (communication of risk information) under the usual conditions in which they will be applied [ 52 ].…”
Section: Discussionmentioning
confidence: 99%